Does digitalization really foster economic growth in the context of the COVID-19 pandemic? - Thi Hoa Nguyen; Minh Khue Nguyen (Asian Development Bank Institute (ADBI), 2024)
This study investigates the impact of digitalization measured by digital competitiveness ranking and digital competitiveness scores on the real economic growth of 63 countries over the period 2017-2021, the period pre and during the COVID-19 pandemic. By employing panel data regression models, this study has revealed that digital competitiveness ranking improved the real GDP growth rates after controlling for several macroeconomic factors, but this positive impact was modest. Both digital competitiveness ranking and digital competitiveness scores had a stronger positive impact on the real economic growth during the pandemic, meaning that they reduced the negative impact of the COVID-19 pandemic on the real GDP growth rates of the studied countries. The findings of this study are robust since endogeneity issues were addressed using the GMM method. Based on these findings, this study offers several implications to policymakers and academicians.
Keywords: O11; O33; O47; O50; 330; digitalization; digital economy; digital competitiveness; economic growth; the COVID-19 pandemic